2002
DOI: 10.1590/s1517-74912002000200003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de desinfetantes de superfície utilizados em Odontologia

Abstract: RESUMO:Desinfecção de superfície é um procedimento realizado nas áreas externas do equipamento odontológico e demais itens do consultório. O objetivo deste trabalho foi analisar a ação de quatro desinfetantes utilizados em Odontologia: álcool etílico a 77°GL, composto fenólico (Duplofen), iodóforo (PVP-I) e solução de álcool etílico a 77°GL com 5% de clorexidina para desinfecção de superfície. Foram analisados quatro pontos em cada equipamento ("carter", pia de lavagem de mãos, encosto de cabeça da cadeira e s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
18

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 12 publications
2
5
0
18
Order By: Relevance
“…However, the results of this research showed that the action of this product was not effective on the bacteria found, corroborating studies that have demonstrated its failure in the disinfection of surfaces when compared to sodium hypochlorite at different concentrations, revealing better antimicrobial activity, with bactericidal, fungicidal and sporicidal properties against the microorganisms tested [8]. The fact that turbidity increased from F4 to F7 in one of the tubes decontaminated with 70% alcohol can be explained by the reduced sample size.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the results of this research showed that the action of this product was not effective on the bacteria found, corroborating studies that have demonstrated its failure in the disinfection of surfaces when compared to sodium hypochlorite at different concentrations, revealing better antimicrobial activity, with bactericidal, fungicidal and sporicidal properties against the microorganisms tested [8]. The fact that turbidity increased from F4 to F7 in one of the tubes decontaminated with 70% alcohol can be explained by the reduced sample size.…”
Section: Discussionsupporting
confidence: 77%
“…The hands of the professional contaminated by saliva and blood are also of fundamental importance in the cross-infection process, when the professional fails to perform a thorough anti-sepsis at the end of the treatment to a patient and beginning of treatment to others [8]. This step is often overlooked by dentists [9].…”
Section: Introductionmentioning
confidence: 99%
“…O presente achado corrobora com estudo sobre a eficácia da clorexidina "in vitro" e "in vivo" em humanos e animais que demonstrou resultado significativo na desinfecção da pele (90) e com outros estudos sobre a higiene das superfícies com a clorexidina (91,92,93) . Ainda na revisão da literatura, foi encontrado apenas um estudo que utilizou a clorexidina alcoólica 2% como desinfetante para os brinquedos, porém não esclarece se o mesmo é de uso de rotina ou apenas para o estudo (94) .…”
Section: Esses Resultados Contrariam a Intenção Proposta Para O Antibunclassified
“…Tal achado no presente estudo vem ao encontro de pesquisas sobre desinfetantes em ambiente odontológico onde observaram a redução significativa de microrganismos com o uso do álcool etílico 70% líquido, embora refiram não ser também o melhor desinfetante testado (91,92) .…”
Section: Esses Resultados Contrariam a Intenção Proposta Para O Antibunclassified
See 1 more Smart Citation